2013
DOI: 10.1074/jbc.m113.501569
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning of the Nuclear and Mitochondrial tRNA 3′-End Processing Activities between Two different Proteins in Schizosaccharomyces pombe

Abstract: Background: Most eukaryotes contain only one tRNase Z gene involved in both nuclear and organellar tRNA 3Ј-end maturation. Results: Schizosaccharomyces pombe has two tRNase Z genes required for nuclear and mitochondrial tRNA 3Ј-end processing, respectively. Conclusion: The evolution of two tRNase Z genes and their differential expression in fission yeast may avoid toxic off-target effects. Significance: The results advance our understanding of tRNA 3Ј-end maturation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…We also investigated the role of S. pombe Trz2 in mt-RNA processing using RNA-seq, which allows comprehensive analysis of the 5 ′ -and 3 ′ -ends of all mt-tRNAs. The data derived from RNA-seq have been verified by comparing them with our previous data obtained with Northern blotting (Zhang et al 2013). We found that while trz2 deletion blocks the 3 ′end processing of all mt-tRNAs, it has varying effects on mt-tRNAs.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…We also investigated the role of S. pombe Trz2 in mt-RNA processing using RNA-seq, which allows comprehensive analysis of the 5 ′ -and 3 ′ -ends of all mt-tRNAs. The data derived from RNA-seq have been verified by comparing them with our previous data obtained with Northern blotting (Zhang et al 2013). We found that while trz2 deletion blocks the 3 ′end processing of all mt-tRNAs, it has varying effects on mt-tRNAs.…”
Section: Discussionsupporting
confidence: 71%
“…The role of tRNase Z L in mt-RNA processing has been studied in S. cerevisiae (Skowronek et al 2014), S. pombe (Zhao et al 2009(Zhao et al , 2010Fan et al 2011;Wang et al 2012;Zhang et al 2013;Zhou et al 2014), Drosophila (Xie and Dubrovsky 2015) and human (In humans, tRNase Z L is named ELAC2) (Brzezniak et al 2011;Sanchez et al 2011). These studies firmly establish that tRNase Z L is responsible for mt-tRNA 3 ′ -end processing.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…First, some species have two genes encoding proteins that modify or process cytosolic or mitochondrial tRNAs differentially, and others use specific isoforms of a single gene product to do so, although there may be no readily apparent evolutionary consistency of the patterns. For example, in most eukaryotes including S. cerevisiae, Drosophila and humans, one tRNase Z (L–refers to long form) gene encodes both nuclear and mitochondrial forms of tRNase Z (L), the enzyme that cleaves the trailer sequences from the 3′ ends of tRNA precursors, whereas (all four) Schizosaccharomyces species contain two essential tRNase Z (L) genes whose products are targeted either to the nucleus or mitochondria [161]. Thus, gene duplications may account for some expansions of tRNA associated enzymes in isolated lineages or species, but with no apparent consistency predictive of outcome without functional studies.…”
Section: Amplification and Diversification Of Eukaryal Trna Methymentioning
confidence: 99%